Predicting tourists' health risk preventative behaviour and travelling satisfaction in Tibet: Combining the theory of planned behaviour and health belief model - Huang, Xingyu; Dai, Shanshan; Xu, Honggang (Tourism management perspectives, 2020)
Both the theory of planned behaviour (TPB) and the health belief model (HBM) are important theories to analyse health-related behaviours; however, few studies have combined these theories to explore health risk issues in the tourism context. This paper explores the relationships underlying travelers' health beliefs, attitudes, self-efficacy, preventative behaviours, and travelling satisfaction during trips to high-altitude destinations. Tibet in China was chosen as the case and the data are analysed by Mplus 7.4 with the WLSMV estimator. The results show that perceived susceptibility and perceived benefit can be regarded as important antecedent beliefs in attitudes toward preventative behaviours; health beliefs and self-efficacy positively influence preventative behaviours; and there are significant indirect relationships from health beliefs to preventative behaviour. Moreover, risk preventative behaviour is found to be a positive determinant of travelling satisfaction during a trip. Findings also revealed that TPB can be supported and extended by combining constructs of HBM. •Health beliefs are important antecedents of preventative behavior.•There are significant indirect relationships from health beliefs to preventative behavior via attitude.•Preventative behavior is a positive determinant of travelling satisfaction.•The TPB and HBM are combined to understand tourist risk preventative behavior and travelling satisfaction.•The TPB is extended by combining constructs of HBM.